Patient satisfaction analysis on service quality of dental health care based on empathy and responsiveness - Fellani Danasra Dewi; Grita Sudjana; Yevis Marty Oesman (Wolters Kluwer Medknow Publications, 2011)
Background: Transformation of health care is underway from sellers' market to consumers' market, where the satisfaction of the patients' need is a primary concern while defining the service quality. Hence, commitment to provide a high-quality service and achieving patients' satisfaction becomes an important issue for dental health care provider. The aim of this research is to investigate the quality of dental health care service based on empathy and responsiveness aspects. Methods: A total of 90 questionnaires were completed by the dental patients who came to dental polyclinic located in Government Hospital, West Java, Indonesia. The questionnaire was concerned on two dimensions of service quality model, i.e. empathy and responsiveness. The obtained data were analyzed using inferential statistics (t test) and also descriptive statistics with importance-performance analysis. Results: All the attributes tested by t test showed that perception and expectation differed significantly, except for responsiveness, i.e. ability of dental assistants in assisting the dentist (t test 0.505<t table 1.987). The most important factor in evaluating patient satisfaction is the response given by administration staff related to long waiting time (t test 5.377), followed by dental assistant's knowledge about the patient's need during treatment (t test 4.822) and explanation that was given by dentist (t test 4.700). Conclusion: It can be inferred from IPA that priority should be given to dentist's communication and dental assistant's knowledge toward patient's needs to enhance the service quality.